2001
DOI: 10.1002/ar.10023
|View full text |Cite
|
Sign up to set email alerts
|

Transient occurrence of 27 kDa heat‐shock protein in the terminal tubule cells during postnatal development of the rat submandibular gland

Abstract: It has been suggested that the 27 kDa heat-shock protein (Hsp27) plays a role at crucial cellular checkpoints for proliferation, apoptosis, and differentiation. We examined the immunolocalization of Hsp27 in the rat submandibular gland during postnatal development, wherein acinar cells proliferate and differentiate at earlier postnatal periods. At 2 weeks of age, weak Hsp27 immunoreactivity was distributed diffusely over all gland components. At 3 weeks, Hsp27 immunoreactivity disappeared in most parts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Until P3-4w, a boundary period between the proliferation and differentiation stages of acinar cells of rat submandibular gland acinar cells, a small number of embryonic type secretory cells termed as terminal tubule (TT) cells remain in developing acini (Chang 1974). We have previously reported that Hsp27-immunoreactivity is temporarily detected in TT cells and its immunoreactivity quickly disappears with the progress of TT cell differentiation (Amano et al 2001). These results suggest that Hsp27 plays as a molecular switch that regulates the transition from the cell proliferation to differentiation.…”
Section: Fixation and Stainingmentioning
confidence: 99%
“…Until P3-4w, a boundary period between the proliferation and differentiation stages of acinar cells of rat submandibular gland acinar cells, a small number of embryonic type secretory cells termed as terminal tubule (TT) cells remain in developing acini (Chang 1974). We have previously reported that Hsp27-immunoreactivity is temporarily detected in TT cells and its immunoreactivity quickly disappears with the progress of TT cell differentiation (Amano et al 2001). These results suggest that Hsp27 plays as a molecular switch that regulates the transition from the cell proliferation to differentiation.…”
Section: Fixation and Stainingmentioning
confidence: 99%
“…Although the localization of iNOS and the HSPss and their roles in normal salivary gland are well documented [1,5,10,21,31], little information is available on their role in neoplasm of salivary gland [4,5]. The present study showed iNOS and the HSPs are widely localized at neoplastic epithelium in pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 44%
“…Both mesenchymal and neoplastic epithelial cells exist in the stromal tissues of pleomorphic adenoma [9]. The expression of iNOS and HSPs in normal salivary glands are observed in epithelial cells such as ductal and myoepithelial cells, but not in stromal cells [1,5,31]. The positive cells in stromal tissues may be neoplastic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations